Urismo de recreación y la oferta turística en el cantón Montalvo - Jaramillo Medina, Isabel Jahaira (2020)
Recreation tourism generates great opportunities, benefiting the tourist who has chosen it, in this way he can perform or choose personalized activities to his liking, in which he can improve his whole being, mind, body, this type of tourism is very productive about everything because you can execute group activities for the benefit of all members, it is usually fun and / or competitive. Montalvo is a very nice canton for its friendly people and for its climate with a rich tropical climate, there are various recreational places to go sightseeing, in this canton we can see several orange fields and its landscape is embroidered by the majestic Andes mountain range. Within the investigation, we will be able to see its location, situation in conflict, scope that will allow to know the existing problems, social relevance, evaluation of the problem, justification, questions of the investigation. The analysis of the observation record will let you know what the possible solution is for recreation tourism and the tourist offer in the canton of Montalvo to be strengthened and spread throughout the country. The questions are totally objective, and where we can know the opinions of its visitors, in order to improve recreation tourism and the tourist offer in the Montalvo canton, promotion strategies, offer of services that will increase and the discounts that will exist and together with the media and social networks they will spread allowing to promote and reach a greater number of tourists.